(untitled) (PJDOL, 2023)
This study was designed was to explore the role of National Vocational and Technical Training commission in the implementation of National Skills Strategies 2009-2013 in context of instructors training. It was descriptive research and survey design in nature. Data was collected from 70 principals, 251 instructors of the vocational institutes across Pakistan by using self-developed questionnaires who were selected by applyingsystematic random sampling technique via self-approach. The collected data was arranged and coded. The coded data was entered into computer for analysis. Inferential and descriptive statistics was applied to analyze the data with help of Statistical Package for social Sciences (SPSS, version 20.0) software.